A novel solution for an efficient tele‐collaborating in surgical medical education: Three‐dimensional tele‐immersion systems. Issue 6 (1st April 2019) - Gahatraj, S.; Alsadoon, Abeer; Prasad, P.W.C.; Haddad, Sami; Alrubaie, Ahmad; Pham, Linh; Deva, Anand; Hsu, Jeremy
Abstract: Three‐dimensional tele‐immersion systems for tele‐collaboration in surgical medical education (SME) have not been implemented due to issues of variable bandwidth availability and delay requirements for high real‐time video quality. The proposed solution in this paper aims to implement a three‐dimensional tele‐immersion system for tele‐collaboration in SME with improved video quality, minimized end‐to‐end delay, and an adaptation ratio, to increase tele‐collaboration experience. The proposed system is based on an algorithm that enhances compression, creates bandwidth adaptivity, and leads to low latency (ECBAaLL), to make efficient use of limited network bandwidth and reduce end‐to‐end delay, by introducing a raptor code and an enhanced algorithm based on segmentation. The results achieved in terms of video quality, end‐to‐end delay, and adaptation ratio of the video streams reflect that the proposed new algorithm improves the quality per stream of the real‐time videos by 8% and reduces the end‐to‐end delay of the video packets by 6%‐7% and that, with the new algorithm, the adaptation ratio of the bandwidth‐adapted videos is increased by 4%‐5%. This work focuses on reducing transmission delays and implementing an improved compression algorithm with reduced end‐to‐end delay and high video adaptation. Hence, the outcome is the quality of video streams for available bandwidth budget with minimal end‐to‐end and processing time delays on a real‐time tele‐collaboration environment in SME. Abstract :